ATXN10 Is Required for Embryonic Heart Development and Maintenance of Epithelial Cell Phenotypes in the Adult Kidney and Pancreas - Bentley-Ford, Melissa R.; Andersen, Reagan S.; Croyle, Mandy J.; Haycraft, Courtney J.; Clearman, Kelsey R.; Foote, Jeremy B.; Reiter, Jeremy F.; Yoder, Bradley K. (Frontiers in Cell and Developmental Biology, 2021)
Atxn10 is a gene known for its role in cytokinesis and is associated with Spinocerebellar Ataxia (SCA10), a slowly progressing cerebellar syndrome caused by an intragenic pentanucleotide repeat expansion. Atxn10 is also implicated in the ciliopathy syndromes Nephronophthisis (NPHP) and Joubert Syndrome (JBTS), which are caused by disruption of cilia function leading to nephron loss, impaired renal function, and cerebellar hypoplasia. How Atxn10 disruption contributes to these disorders remains unknown. Here, we generated Atxn10 congenital and conditional mutant mouse models. Our data indicate that while ATXN10 protein can be detected around the base of the cilium as well as in the cytosol, its loss does not cause overt changes in cilia formation or morphology. Congenital loss of Atxn10 results in embryonic lethality around E10.5 associated with pericardial effusion and loss of trabeculation. Similarly, tissue specific loss of ATXN10 in the developing endothelium (Tie2-Cre) and myocardium (cTnT-Cre) also results in embryonic lethality with severe cardiac malformations occurring in the latter. Using an inducible Cagg-CreER to disrupt Atxn10 systemically at post-natal stages, we show that ATXN10 is also required for survival in adult mice. Loss of ATXN10 results in severe pancreatic and renal abnormalities leading to lethality within a few weeks post ATXN10 deletion in adult mice. Evaluation of these phenotypes further identified rapid epithelial to mesenchymal transition (EMT) in these tissues. In the pancreas, the phenotype includes signs of both acinar to ductal metaplasia and EMT with aberrant cilia formation and severe defects in glucose homeostasis related to pancreatic insufficiency or defects in feeding or nutrient intake. Collectively, this study identifies ATXN10 as an essential protein for survival.